Protecção integrada em tomate de indústria: modelo de previsão do míldio - Mexia, António (2009)
In Portugal, the processing tomato is of great economical importance. The maintenance of the quality of the final product is of growing preoccupation due to the ever increasing consumer demand. IPM has been considered as the best alternative due to the guarantee of some of these demands, in particular the non existence of pesticide residues. The objectives of the work carried out in the Ribatejo were to establish risk assessment methodologies and decision rules for the main enemies of the tomato crop and also to contribute for IPM development in this area. Of these main enemies late blight and the fruitworm are of great importance and determine the treatment schemes. The rationalization of the treatments is based on: the reduction of the fungicide interventions by better timing and the substitution of the insecticides by non chemical alternatives. For the prior we intend to adapt an existing model the “Tom-cast” which is largely used in Mexico. The present study presents the model and describes the first steps that have been taken in validating the model in the conditions of the Ribatejo. The results are an indication of the strong potential of the model. The next two years prospects and orientation are also presented.